Stability studies of titanium–carboxylate complexes: A multi-method computational approach - Omar Abdalazeem A.; Elmarassi Yasser R. M.; Saadawy M.; Musa Abdallah Bashir; Mahmoud Nesrine M. R. (Open Chemistry)
Understanding the stability of metal–ligand complexes is essential for advancing applications in environmental, industrial, and biomedical chemistry; however, titanium coordination systems remain underexplored, particularly with organic ligands of chelating properties. This study aims to evaluate and compare the stability constants of titanium (iv) complexes with propanoic acid and citric acid to better understand their coordination behavior. A multi-method computational approach was employed, integrating point-wise calculation, half-integral, linear plot, and least-squares methods to enhance the accuracy and reproducibility of proton–ligand dissociation constants (pK a) and metal–ligand formation constants (log K). The titanium–propanoate complexes showed moderate stability (log  K 2 = 4.7564, log  K 3 = 4.1015), influenced by steric and electronic factors, while the titanium–citrate complex exhibited a higher binding affinity (log  K 1 = 7.8351), indicating strong chelation capacity. The consistency across all computational and graphical methods validates the reliability of the findings. These insights provide a dependable framework for evaluating titanium-based coordination compounds and may guide future research into their potential applications in environmental and biomedical fields.